Resistance of two potato cultivars with different morphological characteristics to potato tuberworm, Phthorimea operculella (Lepidoptera: Gelechiidae) in field condition - RAJABPOUR, ALI; SHAHBI, MASOUD (The Indian Journal of Agricultural Sciences, 2018)
Potato tuberworm, Phthorimea operculella Zeller, is one of the most important pests of potato in many regions of the world. Resistance of two potato cultivars, Sante and Arinda, with different morphological characteristics to leaf and tuber infestations by the pest were investigated in two research fields. Samplings were performed weekly during two agricultural seasons (2013/2014 and 2014/2015). Results showed that although population density of the pest eggs on the Sante cultivar, with non dense leaf trichome density, was significantly higher than the Arinda cultivar, with dense leaf trichome, but larval density in the Sante cultivar significantly was lower than Arinda. The obtained data showed that damaged tuber yield in the Sante cultivar, with high tuber tissue density, were significantly higher than Arinda cultivar, with low tuber tissue density. No significant difference was observed in the total potato tuber yield (Damaged + no damaged yields). Use of the cultivars with dense leaf trichomes in combination with higher inundative release rate of the parasitoid wasp or other natural enemies of the pest are recommended in integrated pest management program of P. operculella in potato fields.